Exploring Learner Engagement With Multiple Sources of Feedback on L2 Writing Across Genres - Shi, Yali (Frontiers in Psychology, 2021)
While there have been growing amount of research on learner engagement with feedback on L2 writing in the past decade, learners’ multi-dimensional engagement with feedback from multiple sources across different genres has remained under-explored. To address the gaps, this study investigated how six second-year English majors engaged behaviorally, cognitively and affectively with automated, peer and teacher feedback across three genres (argumentation, exposition, and narration) in an L2 writing class given online over a 16-week semester. Through the textual analysis of learners’ drafts, feedback and revision and qualitative analysis of their interview transcripts, it was found that the quantity and incorporation rate of feedback in general, across three feedback sources and two feedback types all differed by genres; surface-level teacher feedback remained the most highly incorporated, though. Learners’ engagement with feedback also varied, suggesting its complexity triggered by the mediating effect of contextual and individual factors plus the interconnectedness and inconsistencies among engagement dimensions. Two pedagogical implications were provided to enhance learner engagement.